Être ou ne pas être à sa place, c’est là la question : à propos du sens de la place des militaires de l’operation Sentinelle dans l’espace public urbain - Arthur Oldra (Territoire en Mouvement)
In places of affluence (touristic, of transports, cultural), this is trivial to cross patrols of soldiers from the Sentinelle operation. Permanently present in some public places since 2001, their number has significantly augmented after the terrorist attacks in january 2015 in Paris. However, before being made visible on the public scene, this is firstly a logical of setting in place that must be performed, from preparation to achievement of the mission. For the military, this implementation is carried out "in situation" by the body during the first patrols, firstly physically in a succession of emplacements but also symbolically during interactions or by games of distances whether with the urban dwellers or other soldiers. Indeed, the places of each are redefined or put in question, establishing a balance of power between the newly arrived soldiers and local users. These situations of interaction reflect a dialectical tension between an occupied location and his social legitimacy. These situations, which express as many games of places and placements, are therefore renegotiated by the action of the patrols of the Sentinelle force. As a result, occupying a place creates a double dimension for the military, an action on space (patrols, prohibitions, etc.) and a reflection (sense of mission, reasons of engagement) of this action. We suggest to present the putting in place of soldiers into the urban public space and then the meaning they made.